2022
DOI: 10.1186/s12906-021-03488-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of selected cardiovascular active natural compounds with CXCR4 and CXCR7 receptors: a molecular docking, molecular dynamics, and pharmacokinetic/toxicity prediction study

Abstract: Background The chemokine CXCL12 and its two receptors (CXCR4 and CXCR7) are involved in inflammation and hematopoietic cell trafficking. This study was designed to investigate molecular docking interactions of four popular cardiovascular-active natural compounds; curcumin, resveratrol, quercetin, and eucalyptol; with these receptors and to predict their drug-like properties. We hypothesize that these compounds can modify CXCL12/CXCR4/CXCR7 pathway offering benefits for coronary artery disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 90 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…ADME (absorption, distribution, metabolism, and excretion) studies, including drug-likeness analysis, are essential in drug discovery, and provide a reasonable decisiveness on whether or not inhibitors should be progressed to a biological system [ 31 ]. A potent antagonistic interaction of inhibitors with a receptor protein or enzyme can not guarantee the ability of an inhibitor to act as a drug; therefore, ADME assessment is essential in drug development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ADME (absorption, distribution, metabolism, and excretion) studies, including drug-likeness analysis, are essential in drug discovery, and provide a reasonable decisiveness on whether or not inhibitors should be progressed to a biological system [ 31 ]. A potent antagonistic interaction of inhibitors with a receptor protein or enzyme can not guarantee the ability of an inhibitor to act as a drug; therefore, ADME assessment is essential in drug development.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting Tanimoto coefficient is fingerprint-based, encoding each molecule to a fingerprint “bit” position (MACCS), with each bit recording the presence (“1”) or absence (“0”) of a fragment of the molecule. Interpretation of the probability of toxicity for compounds 4b and 13a can be explained by the cytotoxicity diagram [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that β-pinene is a bioactive compound with antioxidant, cytoprotective, and neuroprotective effects [ 22 , 23 ]. Eucalyptol, the most abundant component of Oleum Cinnamomi , has promising potential for cardiovascular disease [ 24 ]. As a strong natural antioxidant substance, p -cymene has antioxidant activities and is effective for the treatment of some severe diseases, such as cancer, diabetes, and coronary heart disease [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A molecular modeling investigation using the Molecular Operating Environment (MOE) (Murad et al 2022;Al-Rajh et al 2022c) module was conducted to explain the observed insecticidal activity of chitinase. The structural model was built utilizing the 'BUILDER' module of MOE.…”
Section: Molecular Dockingmentioning
confidence: 99%